(untitled) (Indian Journal of Nematology, 2024)
A study was conducted to assess the effect of individual and combined application of Trichoderma viride and other organic amendments on plant growth and nematode multiplication parameters in comparison with chemical, carbofuran 3G and untreated check for management of root-knot nematodes under polyhouse in Bihar. Maximum improvement in the plant growth parameters was observed with combined application of T. viride @ 10 g /pot + neem cake @ 100 g/pot. Carbofuran 3G @ 2 kg a.i./ha was found most effective in controlling root knot nematodes. T. viride @ 10 g/pot + neem cake @ 100 g/pot increased crop yield by 77 %, compared to 60 % with carbofuran. Neem cake had increased the efficiency of the biocontrol agent, which might be partially due to reduction in nematode population by the action of toxicity of fungal bio agents and partly to the fact that neem cake additive served as manure for management of M. incognita.